Integrasi budaya lokal dalam bilingual storynomics tourism untuk pemberdayaan remaja tidak sekolah di Desa Wisata Ara, Bulukumba - Andi Nurhikmah; Anugerah Febrian Syam; Rina Asrini Bakri; Rahayu Rahayu; Fitriani Fitriani (Penamas: Journal of Community Service, 2026)
This community service initiative aimed to implement Local Culture-Based Bilingual Storynomics Tourism to strengthen global literacy and bilingual narrative competence among non-school adolescents in Ara Tourism Village, Bontobahari District, Bulukumba Regency. The program adopted a Participatory Action Research (PAR) framework involving 15 participants through four stages: diagnostic cultural mapping, co-design of bilingual tourism narratives, experiential simulation through role-play activities, and reflective evaluation. Pre-intervention assessment indicated a low overall literacy score of 2.1 on a four-point scale, reflecting limited communicative confidence and narrative coherence in English. Following the intervention, the average score increased to 3.2, representing a measurable improvement of approximately 52% across assessed indicators. Improvements were observed in communicative confidence, narrative structure, and the integration of local cultural elements into tourism storytelling. All participants were able to incorporate elements of local maritime heritage into simple bilingual narratives. These findings suggest that integrating local culture with participatory bilingual storytelling practices can support the development of communicative competence and strengthen youth engagement in community-based tourism.